The effect of remimazolam and propofol on post-hysteroscopy sleep quality under general anesthesia: a post hoc analysis - Yang, Chen; Zhang, Le; Cheng, Yan; Hu, Jianying; Nie, Yuyan; Sun, Shen; Huang, Shaoqiang (Frontiers in Pharmacology, 2025)
BackgroundThis post hoc analysis trial compared the impacts of remimazolam and propofol anesthesia on sleep quality and fatigue after hysteroscopic surgery.MethodsThe post hoc analysis excluded patients with a Pittsburgh Sleep Quality Index (PSQI) score >15 or incomplete data. Preoperative PSQI scores were compared between patients receiving remimazolam and propofol. Intraoperative monitoring was conducted using the Modified Observer’s Assessment of Alertness/Sedation (MOAA/S) scale. Postoperative sleep and fatigue were assessed using the Athens Insomnia Scale (AIS) and Fatigue Scale-14 (FS-14) via WeChat questionnaires on the first and second postoperative days.ResultsFifteen patients were included in this post hoc analysis. No significant differences were observed in AIS scores on postoperative days 1 and 2. Compared to the remimazolam group, patients in the propofol group experienced more awakenings (1 [0, 2] vs. 2 [1, 3], p = 0.029) and poorer sleep quality (1 [0, 2] vs. 2 [1, 2], p = 0.043) on the first postoperative day. FS-14 scores indicated higher fatigue in the propofol group on the first postoperative day (5 [3, 8] vs. 3 [2, 6], p = 0.035) with no significant difference on the second day. No intraoperative awareness was reported, and anesthesia satisfaction was similar between the two groups.ConclusionThe post hoc analysis revealed that remimazolam reduced fatigue, particularly mental fatigue, on the first postoperative day compared to propofol in patients undergoing hysteroscopic surgery, despite no significant differences in AIS scores. Further research is needed to explore these effects in longer surgical procedures.